A triclinic polymorph of cyclo-tetra - Thio-saccharinato- 8 S:S-tetra-kis[(triphenyl-phosphane-P)silver(I)] - Dennehy, Mariana (2012)
The triclinic structure of the title compound, cyclo-tetra-kis-(-1,1-dioxo- 1 6,2-benzothia-zole-3-thiol-ato- 2 S:S)tetra-kis- [(triphenyl-phosphane-P)silver(I)], [Ag4(C7H4NO2S2)4(C18H15P)4], is a polymorph of the previously reported monoclinic structure [Dennehy, Mandolesi, Quinzani & Jennings (2007). Z. Anorg. Allg. Chem. 633, 2746-2752]. In both polymorphs, the complex lies on a crystallographic inversion centre and the bond distances are closely comparable. Some differences can be found in the inter-atomic angles and torsion angles involving the inner Ag4S4 skeleton. The polymorphs contain essentially identical two-dimensional layers, but with different layer stacking arrangements. In the triclinic form, all layers are related by lattice translation, while in the monoclinic form they are arranged around glide planes so that adjacent layers are mirrored with respect to each other.